Transcriptional Profile and Structural Conservation of SUMO-Specific Proteases in Schistosoma mansoni - Roberta Verciano Pereira; Fernanda Janku Cabral; Matheus de Souza Gomes; Liana Konovaloff Jannotti-Passos; William Castro-Borges; Renata Guerra-Sá (Journal of Parasitology Research)
Small ubiquitin-related modifier (SUMO) is involved in numerous cellular processes including protein localization, transcription, and cell cycle control. SUMOylation is a dynamic process, catalyzed by three SUMO-specific enzymes and reversed by Sentrin/SUMO-specific proteases (SENPs). Here we report the characterization of these proteases in Schistosoma mansoni. Using in silico analysis, we identified two SENPs sequences, orthologs of mammalian SENP1 and SENP7, confirming their identities and conservation through phylogenetic analysis. In addition, the transcript levels of Smsenp1/7 in cercariae, adult worms, and in vitro cultivated schistosomula were measured by qRT-PCR. Our data revealed upregulation of the Smsenp1/7 transcripts in cercariae and early schistosomula, followed by a marked differential gene expression in the other analyzed stages. However, no significant difference in expression profile between the paralogs was observed for the analyzed stages. Furthermore, in order to detect deSUMOylating capabilities in crude parasite extracts, SmSENP1 enzymatic activity was evaluated using SUMO-1-AMC substrate. The endopeptidase activity related to SUMO-1 precursor processing did not differ significantly between cercariae and adult worms. Taken together, these results support the developmentally regulated expression of SUMO-specific proteases in S. mansoni.